Michelman unveils new family of Hydrosize carbon fibre sizing solutions. Issue 12 (December 2018) - Unknown
Abstract : Sizing agent specialist Michelman of Cincinnati, OH, USA, has introduced a new range of Hydrosize carbon fibre sizing solutions. According to the company, the new product family demonstrates its commitment to carbon fibre manufacturers and will allow the composites industry to further exploit the beneficial high strength and stiffness of carbon fibre. The introductions were presented at the CAMX 2018 expo in Dallas in October.